Dump Postmodern sculpture in the dissolved field. - Godo, Randi E.V.; Kroksnes, Andrea (Oslo : National Museum of Art, Architecture and Design Oslo, 2007)
Braein, Kristina ; Demming, Dagmar ; Freuchen, Jan ; Genzken, Isa ; Gundersen, Jon ; Guyton, Wade ; Karlsen, Inghild ; Knoebel, Imi ; Kounellis, Jannis ; Kurdol, Egil Martin ; Lawler, Louise ; Lertchaiprasert, Kamin ; LeWitt, Sol ; Low, Camilla ; Mirra, Helen ; O'Donnell, Michael ; Rothschild, Eva ; Ruthenbeck, Reiner ; Serra, Richard ; Smithson, Robert ; Waerenskjold, Camilla ; Walker, Kelley ; West, Franz ; Ytterstad, Snorre
geboortedatum per kunstenaar
Engels
Noors
Exhibition. Dump : Postmodern sculpture in the dissolved field. National Museum of Art, Architecture and Design Oslo, 03.05.2007 - 19.08.2007.
boek